Financial Literacy and Love of Money as Determinants of Gen Z Students’ Personal Financial Management: The Mediating Role of Financial Self-Efficacy - Ni Wayan Novi Budiasni; Kadek Arik Darmayanti (INVEST : Jurnal Inovasi Bisnis dan Akuntansi, 2025)
The purpose of this study was to examine the effects of Financial Literacy, Love of Money, and Financial Self-Efficacy on Personal Financial Management among Gen Z students at the Satya Dharma College of Economics, with Financial Self-Efficacy as a mediating variable. The study utilized 20 indicators and involved 100 respondents. The results indicate that Financial Literacy positively affects both Personal Financial Management and Financial Self-Efficacy. Additionally, Financial Self-Efficacy positively influences Personal Financial Management and acts as a mediator between Financial Literacy and Personal Financial Management. Furthermore, Love of Money positively affects Financial Self-Efficacy; however, it does not have a positive effect on Personal Financial Management either directly or through Financial Self-Efficacy mediation.